Investigation study to achieve a logarithmic reduction strategy for load shedding based on priority demand - F. Hasan, Yasir; M. Tuaimah, Firas (International Journal of Engineering and Technology, 2019)
Many countries around the globe suffer from a long time power shortage as a result of excess load, lack of generation, and inefficient distribution networks. The load shedding scheme has been extremely implemented as a fast solution for unbalance conditions. Therefore, load shedding is crucial to investigate supply-demand balancing in order to protect the network from collapsing and to sustain stability as possible; however, its implementation is mostly undesirable. The conventional methods of load shedding lead to over or under shedding and this may lead to many problems with the network. Under the scheme, these methods disconnect the load or the entire feeder without considering their priorities and may not perform as anticipated. In this work, we propose a logarithmic reduction method to reduce the load according to the priority and day life criticality. The method for shedding the loads base on Reduction Matrix and which in turn depend on the priority demands. The higher priority demands are fed with a reliable power source by the real-time monitoring of the network accompanied with power reducing for the lower priority demands. We test a real data sample provided by the Iraqi national grid control center in Baghdad. Our simulation results prove the effectiveness and practicality of the applied method paving the way for possible applications in power systems.Â Â